2020
DOI: 10.1111/ijcp.13841
|View full text |Cite
|
Sign up to set email alerts
|

Trends, management and outcomes of acute myocardial infarction in chronic liver disease

Abstract: Aims There are limited data on the management and outcomes of chronic liver disease (CLD) patients presenting with acute myocardial infarction (AMI), particularly according to the subtype of CLD. Methods Using the Nationwide Inpatient Sample (2004‐2015), we examined outcomes of AMI patients stratified by severity and sub‐types of CLD. Multivariable logistic regression was performed to assess the adjusted odds ratios (aOR) of receipt of invasive management and adverse outcomes in CLD groups compared with no‐CLD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Large PCI studies have shown worse clinical outcomes in patients with CLD compared with patients without liver disease and have identified a number of factors leading to an increased risk of adverse events in patients with CLD after PCI 8–12 . De Ritis ratio is a readily available marker of liver disease 2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Large PCI studies have shown worse clinical outcomes in patients with CLD compared with patients without liver disease and have identified a number of factors leading to an increased risk of adverse events in patients with CLD after PCI 8–12 . De Ritis ratio is a readily available marker of liver disease 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Large PCI studies have shown worse clinical outcomes in patients with CLD compared with patients without liver disease and have identified a number of factors leading to an increased risk of adverse events in patients with CLD after PCI. [8][9][10][11][12] De Ritis ratio is a readily available marker of liver disease. 2 An association of De Ritis ratio with an increased risk of mortality has been reported in patients with acute myocardial infarction, 15,16 type 2 diabetes, 27 arterial hypertension, 28 and contrast-induced acute kidney injury after elective PCI.…”
Section: F I G U R E 1 Kaplan-meier Curves Of Mortality Hr Hazard Ratiomentioning
confidence: 99%
See 2 more Smart Citations